Obstetric and neonatal outcome in patients with anxiety disorders. (September 2014) - Pavlov, Michael; Steiner, Naama; Kessous, Roy; Weintraub, Adi Y.; Sheiner, Eyal
Abstract Objective: To investigate whether a diagnosis of anxiety disorder is a risk factor for adverse obstetric and neonatal outcome. Methods: A retrospective population-based study was conducted comparing obstetric and neonatal complications in patients with and without a diagnosis of anxiety. Multivariable analysis was performed to control for confounders. Results: During the study period 256 312 singleton deliveries have occurred, out of which 224 (0.09%) were in patients with a diagnosis of an anxiety disorder. Patients with anxiety disorders were older (32.17 ± 5.1 versus 28.56 ± 5.9), were more likely to be smokers (7.1% versus 1.1%) and had a higher rate of preterm deliveries (PTD; 15.2% versus 7.9%), as compared with the comparison group. Using a multiple logistic regression model, anxiety disorders were independently associated with advanced maternal age (OR 1.087; 95% CI 1.06–1.11; p = 0.001), smoking (OR 4.51; 95% CI 2.6–7.29; p = 0.001) and preterm labor (OR 1.92; 95% CI 1.32-–2.8; p = 0.001). In addition, having a diagnosis of an anxiety disorder was found to be an independent risk factor for cesarean section (adjusted OR 2.5; 95% CI 1.82–3.46; p < 0.001), using another multivariable model. No association was noted between anxiety disorders and adverse neonatal outcomes including small for gestational age, low Apgar scores and perinatal mortality. Conclusion: Anxiety disorders are independent risk factors for spontaneous preterm delivery and cesarean section, but in our population it is not associated with adverse perinatal outcome.